The efficacy and safety of ciclesonide for the treatment of perennial allergic rhinitis: a systematic review and meta-analysis - Yang,Qi (2019)
Abstract Introduction: Allergic rhinitis is a chronic inflammatory disease which affects 1 out of 6 individuals. Perennial allergic rhinitis accounts for 40% of AR cases. Ciclesonide is one of the relatively new intranasal steroid for allergic rhinitis. Objective: The purpose of this study was to evaluate the efficacy and safety of ciclesonide in the treatment of perennial allergic rhinitis. Methods: We searched Pubmed, Scientific Citation Index, Embase, Clinical Trial Registries for randomized controlled trials and Cochrane Central Register of Controlled Trials to find out the randomized controlled Trial comparing ciclesonide with placebo for PAR. Results: Eight studies were included. In comparison with placebo groups, ciclesonide groups significantly decreased Reflective Total Nasal Symptom Score (MD = −0.56; 95% CI −0.72 to 0.39, p < 0.00001) with heterogeneity (p = 0.19, I2 = 24%), Instantaneous Total Nasal Symptom Score (MD = −0.57; 95% CI −0.75 to −0.39, p < 0.00001) with heterogeneity (p = 0.34, I2 = 11%). A significant effect for Reflective Nasal Symptom Score Subtotal (MD = −0.15; 95% CI −0.18 to −0.13, p < 0.00001) with heterogeneity (p = 0.12, I2 = 24%) was also demonstrated. Rhinoconjunctivitis quality of life questionnaire score (RQLQs) (MD = −0.27; 95% CI −0.39 to −0.15, p < 0.00001) with heterogeneity (p = 0.58, I 2 = 0%) in the treatment of ciclesonide was also significantly reduced. In addition, the difference in Treatment-Emergent Adverse Events between the two groups was not significant. Conclusion: Ciclesonide can improve perennial allergic rhinitis without increasing adverse events. Ciclesonide may be another valuable choice for perennial allergic rhinitis in the future.